A conceptual framework for multi-objective facility layout planning by a bottom-up approach - Pablo Pérez-Gosende; Josefa Mula; Manuel Díaz-Madroñero (International Journal of Production Management and Engineering, 2023)
The purpose of this paper is to present a conceptual framework to facilitate academics and practitioners’ decision making related to multi-objective facility layout planning (mFLP) by employing a bottom-up approach. Based on a literature survey framed in the mFLP context, this work identified and discussed a set of criteria that have become limitations of the traditional top-down approach. These criteria served as the basis to conceive the proposed conceptual framework. Our conceptual framework formalises FLP as a multi-objective problem by following the two traditional planning phases (block- and detailed phase) in reverse by a bottom-up approach, and by also integrating a third phase, called the refined phase, which has not previously been contemplated in the literature. Apart from identifying the inputs and outputs of each phase, the conceptual framework groups together several objectives related to mFLP that have been recently considered in the literature and formalises and contextualises them according to the planning phase in which they are involved. This is the first time that mFLP is addressed with a bottom-up approach.